Public management in the sphere of information security and democracy development in Ukraine in war time - Semenets-Orlova, Inna; Klochko, Anatolii; Amro, Taiier (My University, 2022)
The article states that the current stage in the formation and implementation of Ukraine’s national security strategy is related to the need to protect its national interests in the face of new threats to its state sovereignty and territorial integrity. It was found that they determine the basic principles and current threats to national security, the relevant goals, as well as mechanisms to protect the national interests of Ukraine. It is proved that the main goal of Ukraine’s state policy is to further strengthen national security as a key factor in sustainable social development. У статті зазначено, що сучасний етап формування та реалізації стратегії національної безпеки України пов’язаний з необхідністю захисту її національних інтересів в умовах нових загроз її державному суверенітету та територіальній цілісності. Визначено основні принципи та актуальні загрози національній безпеці, відповідні цілі, а також механізми захисту національних інтересів України. Доведено, що основною метою державної політики України є подальше зміцнення національної безпеки як ключового чинника сталого суспільного розвитку.
Keywords: national security; національна безпека; hybrid war; гібридна війна; democracy; демократія